Study of Entrepreneurial Literacy and Digital Literacy on Business Sustainability Mushroom Cultivation in Beruk Village, Jatiyoso District, Karanganyar Regency - Halimah; Silfa, Amanda; Adiyani, Rini; Wijiastuti, Sri; Kurniawati, Susilaningtyas Budiana; Widodo, Zandra Dwanita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article discusses the sustainability of the mushroom cultivation business in Beruk Village, Jatiyoso District, Karanganyar Regency. This research focuses on three variables, namely entrepreneurial literacy, digital literacy, and business sustainability. This study uses qualitative methods and direct observation of the subject with interview-based data collection which is then examined using a qualitative approach technique. The results of this study indicate that entrepreneurial literacy and digital literacy in mushroom cultivation business actors in Beruk Village, Jatiyoso District, Karanganyar Regency can be categorized as quite good because the mushroom cultivation business actors already have an understanding of the business being established. Meanwhile, business continuity shows that the mushroom cultivation business is quite good because it can develop well